2018
DOI: 10.1159/000487946
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of Endometrial Polyps in Infertile Patients with Endometriosis

Abstract: Aim: To study whether infertile patients with endometriosis have a higher prevalence of endometrial polyps, and to clarify the characteristics of the pathology of combined polyps. Methods: Infertile patients who had undergone both hysteroscopy and laparoscopy in Reproductive Hospital Affiliated with Shandong University from January 2014 to May 2017 were enrolled. Patients with and without endometriosis, diagnosed by laparoscopy, were staged and included in the study group and control group, respectively, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Reduced implantation, clinical pregnancy rate, ongoing pregnancy and live birth rate was found in women with endometriosis placing sibling oocytes from same donor, comparing women without endometriosis [13]. We also found that higher prevalence of endometrial ployps in infertile patients with endometriosis, implying the special character of eutopic endometrium in endometriosis, which also impair embryo implantation [14].Animal studies support clinical data suggesting that endometriosis leads to implantation defects, again implicating the endometrium. Induction of endometriosis in animals demonstrates similar phenotypes to human disease [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…Reduced implantation, clinical pregnancy rate, ongoing pregnancy and live birth rate was found in women with endometriosis placing sibling oocytes from same donor, comparing women without endometriosis [13]. We also found that higher prevalence of endometrial ployps in infertile patients with endometriosis, implying the special character of eutopic endometrium in endometriosis, which also impair embryo implantation [14].Animal studies support clinical data suggesting that endometriosis leads to implantation defects, again implicating the endometrium. Induction of endometriosis in animals demonstrates similar phenotypes to human disease [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…60 Infertile patients with endometriosis were reported to have a higher prevalence of endometrial polyps, and these polyps were often combined with simple hyperplasia. 61…”
Section: Infertilitymentioning
confidence: 99%
“…Surprisingly, the majority of pregnancies happened naturally before the first IUI round. The systematic review by Zhang et al, (14) According to the researchers, the influence of endometrial polyps and hysteroscopic polypectomy on pregnancy outcomes following assisted reproductive technologies remains unknown. The current systematic study found that hysteroscopic removal of endometrial polyps less than 2 cm in diameter was linked to higher clinical pregnancy rates after IUI.…”
Section: Discussionmentioning
confidence: 99%